An Effective Chaos-Based Image Encryption Scheme Using Imitating Jigsaw Method - Zhen Li; Changgen Peng; Weijie Tan; Liangrong Li (Complexity)
In this paper, an efficient chaos-based image encryption scheme is proposed, which uses the imitating jigsaw method containing revolving and shifting operations. In this scheme, there are three processes in encryption: preprocessing, encryption process, and postprocessing. In the preprocessing, the original image is partitioned into 64 × 64 pixel image blocks and then randomly revolved and shifted under control sequences which are generated by the hyperchaotic Lorenz system whose initial conditions are calculated by original image and keys. Therefore, the preprocessing is sensitive to plain image against differential attacks. In the encryption process, the after-preprocessing image is partitioned into 32 × 32 pixel image blocks; next they are randomly revolved and encrypted by control sequence and key blocks which are generated by the skew tent map. In postprocessing, the after-encryption image is partitioned into 16 × 16 pixels’ image blocks, and they are randomly revolved and shifted again under control sequences which are related with encrypted image and keys. The postprocessing further increases the diffusion characteristics. Moreover, the test experiment and security analyses are given; the results show that our proposed cryptosystem has both security and speed performance.